The Effect Of Capital Structure And Profit Growth On Company Value With Financial Performance As A Moderating Variable In Food & Beverage Sub-Sector Companies On The Idx In 2019-2023 - ruldawati, mayang; ruldawati, Lusiana; Silvia Sari (Profesional Muda Cendekia Publishing, 2025)
Research Aims: The results of the study indicate that a) Capital Structure no significant effect on Company Value b) Profit Growth no significant positive effect on Company Value c) Financial Performance is unable to moderate the positive and significant effect of Capital Structure on Company Value d) Financial Performance is able to moderate the positive and significant effect of Profit Growth on Company Value. Design/methodology/approach: this research The sampling technique used is the purposive sampling method. Purposive sampling is a sampling determination technique with certain considerations. The population in this study is all Food & Beverage Companies listed on the Indonesia Stock Exchange. The population of Food & Beverage companies in this study amounted to 95 companies. Research Findings: this research provides insight that in the context of food and beverage sub-sector manufacturing companies, profit growth plays a greater role in influencing company value than capital structure. This study suggests that companies need to focus more on sales to increase profits in order to drive financial performance to provide better company value. Theoretical Contribution/Originality: this research contributes to The food and beverage industry has unique characteristics, such as sensitivity to raw material prices, relatively stable demand, and reliance on branding strategies. tested the relevance of pecking order theory, trade-off, and profit signals in the food and beverage industry. Its originality lies in the use of financial performance as a moderating variable and the focus on profit growth as the main factor influencing firm value. Keywords: Capital Structure; Profit Growth; Company Value; Financial Performance.